BASED LEARNING MEDIA IN CLASS X STUDENTS OF SMAN 8 BENGKULU CITY - Farenza, Gita; Susanto, Edy; Fitria, Yenni (Journal Of Dehasen Educational Review, 2022)
The purpose of this research:to knowUtilization of Audio Visual-Based Learning Media in Class X Students of SMAN 8 Bengkulu City. The qualitative research method utilizes and analyzes practically and objectively about the Utilization of Audio Visual-Based Learning Media in Class X Students of SMAN 8 Bengkulu City. The steps of this research are observation, interview and documentation. The results of the research on the use of media in ICT subjects at SMA Negeri 8 Bengkulu city that are used and applied are audio-visual media, because this audio-visual media is a media that involves all the senses, namely sight, hearing and so on. Video media can produce sound and moving images, and power point is media that produces interesting images, because this power point can use varied letters and colors can be changed. So that the use of power point media and films/videos is very suitable for ICT subjects.